See breeze like cloud-free zones during Monsoon months - MANDAL , J. C.; HALDER , S. R. (MAUSAM, 1992)
Characteristic features of district cloud-free zones and their day to day evolution along Indian coasts as observed in INSAT cloud imageries during southwest monsoon months have been analysed and discussed along with sea surface and surface air temperatures and monsoon condition situation. It was a weak or break monsoon condition. Appearance of early morning clear zone just off shore along Indian Peninsula coasts is attributed to the gradual lowering of sea surface temperate due to upwelling caused by persistent favorable surface wind and slow-setting of air above colder water. With the advance of the day, wide extension of clear area over water where it ends abruptly and propagation of front-like zone inland manifest as a typical sea breeze. It is postulated that this is the effect of sea breeze circulation and shrinking of air above colder water. It is inferred that time-to-time appearance of such phenomenon may be an Indication of longer weak or break monsoon over the Peninsula.